Pakistan : Finding the Path to Job-Enhancing Growth - World Bank (Islamabad: World Bank, 2013)
Pakistan's rebound from the global financial crisis has been slow and fragile, and unless the economy changes course swiftly, it could face its second balance of payments crisis in five years. Its recovery from the 2008-09 global financial crisis has been the weakest in South Asia, with a double dip pattern. This report identifies conditions for a sustainable job-enhancing growth agenda for Pakistan. Policy must target both goals as they are closely intertwined. Higher growth rates can be achieved through productivity improvements (technology, innovation, better economic governance), but also from higher output extracted from factors-physical capital, labor, human capital, and land. This report considers whether Pakistan should pursue historical growth of 4.3 percent a year, supported by piecemeal structural reforms leading to partial and unsatisfactory outcomes-or rapid growth of 7 percent, requiring comprehensive big-bang reforms. The report is organized around three major themes: (i) the stylized facts, what are the pluses and minuses of Pakistan's patterns of growth and job creation? (ii) the diagnostics, what is holding back Pakistan's growth? And (iii) the transformational agenda, what are the core ingredients of job-enhancing growth? And how can analysis of the political economy identify policy tradeoffs?